Sie sind auf Seite 1von 18

Differential Calculus Integral Calculus

Differentiation Integration/
anti-differentiation

derivative integral
differential

Given: The function, 𝒚 The differential, 𝒅𝒚


Required: Find the derivative or
differential, The integral or the function,
𝒚
𝒅𝒚
, 𝒅𝒚
𝒅𝒙 Hence, integration or anti-differentiation
and differentiation are also known as
𝒅𝒚 inverse operations.
Note: 𝒅𝒚 = 𝒅𝒙
𝒅𝒙
BUT WHAT ARE INVERSE OPERATIONS?
Addition and subtraction multiplication and division
raising to powers and extracting roots
Illustration 1

Given Operation Inverse Answer


Operation
𝟗 𝟗 + 𝟑 = 𝟏𝟐 𝟏𝟐 −𝟑 =𝟗

𝟒 𝟒 𝟖 = 𝟑𝟐 𝟑𝟐 =𝟒
𝟖
𝟐
𝟓𝒙 𝟓𝒙 = 𝟐𝟓𝒙𝟐 𝟐𝟓𝒙𝟐 = 𝟓𝒙
Differentiation
Integration / antidifferentiation
𝒅𝒊𝒇𝒇𝒆𝒓𝒆𝒏𝒕𝒊𝒂𝒍, Inverse
operations 𝒊𝒏𝒕𝒆𝒈𝒓𝒂𝒍, න.
𝒅

Illustration 2.

Given Operation Inverse Operation Answer

𝟖𝒙𝟑 𝒅 𝟖𝒙𝟑 = 𝟐𝟒𝒙𝟐 𝒅𝒙 න𝟐𝟒𝒙𝟐 𝒅𝒙 = 𝟖𝒙𝟑

𝟒𝒙𝟐 − 𝒙 𝒅 𝟒𝒙𝟐 − 𝒙 = 𝟖𝒙 − 𝟏 𝒅𝒙 න 𝟖𝒙 − 𝟏 𝒅𝒙 = 𝟒𝒙𝟐 − 𝒙

𝟑(𝒙 − 𝟑)𝟐 𝒅 𝟑(𝒙 − 𝟑)𝟐 = 𝟔 𝒙 − 𝟑 𝒅𝒙 න𝟔 𝒙 − 𝟑 𝒅𝒙 = 𝟑(𝒙 − 𝟑)𝟐


Illustration 3. Consider the following functions
𝒇(𝒙) = 𝟑𝒙𝟐 , 𝒅 𝟑𝒙𝟐 = 𝟔𝒙𝒅𝒙
𝑭(𝒙) = 𝟑𝒙𝟐 + 𝟏𝟎𝟎 , 𝒅 𝟑𝒙𝟐 + 𝟏𝟎𝟎 = 𝟔𝒙𝒅𝒙
𝑮(𝒙) = 𝟑𝒙𝟐 – 𝟑 , 𝒅 𝟑𝒙𝟐 − 𝟑 = 𝟔𝒙𝒅𝒙
𝑯(𝒙) = 𝟑𝒙𝟐 + 𝟓 , 𝒅 𝟑𝒙𝟐 + 𝟓 = 𝟔𝒙𝒅𝒙

Applying the inverse operation; Summarize the answers;


න𝟔𝒙𝒅𝒙 = 𝟑𝒙𝟐 න𝟔𝒙𝒅𝒙 = 𝟑𝒙𝟐 + 𝒄 Indefinite Integral
= 𝟑𝒙𝟐 + 𝟏𝟎𝟎
where: 𝒄 is called an arbitrary constant
= 𝟑𝒙𝟐 – 𝟑
also called constant of integration
= 𝟑𝒙𝟐 + 𝟓 𝒅
Note: 𝟑𝒙𝟐 = 𝟔𝒙
𝒅𝒙
DEFINITION OF INDEFINITE INTEGRAL
න𝒇′ 𝒙 𝒅𝒙 = 𝒇 𝒙 + 𝒄

where: 𝒇′(𝒙)𝒅𝒙 is called the integrand (𝒇′ 𝒙 𝒅𝒙 is the differential of


the unknown function)
𝒇(𝒙) + 𝒄 is the unknown function (Indefinite Integral)
“The integral of a given differential of a function is equal to the function
itself plus the arbitrary constant.”
න𝒅𝒖 = 𝒖 + 𝒄

Properties of Indefinite Integral

𝟏. න 𝒅𝒖 + 𝒅𝒗 + ⋯ + 𝒅𝒙 = න𝒅𝒖 + න𝒅𝒗 + ⋯ + න𝒅𝒙

𝟐. න𝒂𝒅𝒖 = 𝒂 න𝒅𝒖
𝟏
𝟏 where: is called the correction factor
𝟑. න𝒅𝒖 = න𝒂 𝒅𝒖 𝒂
𝒂
Derivation of more Indefinite Integration Formulas
𝟏. න𝒅𝒖
𝒅𝒖
𝒖 = 𝒖+ 𝑪 (𝟏)

𝟐. 𝒅 𝒖𝒏+𝟏 = (𝒏 + 𝟏)𝒖𝒏 𝒅𝒖

Applying the inverse operation, න(𝒏 + 𝟏)𝒖𝒏 𝒅𝒖 = 𝒖𝒏+𝟏 +𝒄

Applying the second property of


(𝒏 + 𝟏) න𝒖𝒏 𝒅𝒖 = 𝒖𝒏+𝟏 + 𝒄
indefinite integral,
𝒏+𝟏
𝒖 𝒄
Divide by the constant (𝒏 + 𝟏) 𝒏
න 𝒖 𝒅𝒖 = +
𝒏+𝟏 𝒏+𝟏

𝒏+𝟏
𝒖
Power Formula of Integration: න 𝒖𝒏 𝒅𝒖 = +𝑪 (𝟐)
𝒏+𝟏

where: 𝒏 ≠ −𝟏
Steps in integrating an indefinite integral using Power Formula:
a. When necessary, write the given integrand in the 𝒖𝒏 𝒅𝒖 form.
b. From the integrand, choose a factor which gives the possible value of 𝒏 and 𝒖, taking
note that 𝒏 is a constant and 𝒖 is a function that contains the variable of integration,
as indicated in the factor 𝒅𝒖.
c. Evaluate the value of 𝒅𝒖 from the defined possible value of 𝒖 in step b.
d. Write the new function by reciting the left side of the formula and writing the value of
each element 𝒖, 𝒏, and 𝒅𝒖 from steps b and c.
e. Compare the resulting new function in step d to the function in the preceding step.
(i) If the new function is equal to the given function, apply the right side of the formula;
(ii) If they differ by a constant factor only, then multiply the correction factor into this
new function and apply the right side of the formula;
(iii) If the two functions differ by a factor which involves the variable of integration,
erase this trial solution. Try another factor, if there is any, which may be assumed to
represent 𝒖𝒏 and perform steps a-e. If (i) is still not obtained, write the given
integrand in another form by expansion, factoring or substituting another variable,
whichever is best applicable.
𝒅𝒙
Example 1. Evaluate න To check if the
𝒙
Solution: obtained indefinite
integral is correct,
𝒅𝒙
න = න𝒙−𝟏Τ𝟐 𝒅𝒙 differentiate the final
𝒙 answer.
𝒏+𝟏
𝒖
Apply Power Formula(PF); න𝒖𝒏 𝒅𝒖 = +𝑪
𝒏+𝟏
𝟏 𝒅𝒙
𝒏 =− 𝒅 𝟐 𝒙 + 𝑪 ?=
𝟐 𝒙
𝒖= 𝒙
𝒅𝒙 𝒅𝒙
𝒅𝒖 = 𝒅𝒙 𝟐∙ + 𝒅𝑪 =
𝟐 𝒙 𝒙
The new function,
𝟏 𝟏 𝒅𝒙 𝒅𝒙
− +𝟏
𝒙 𝟐 𝒙𝟐 =
= න𝒙− 𝟏
Τ𝟐 𝒙 𝒙
𝒅𝒙 = 𝟏
+ 𝑪 = 𝟏 + 𝑪
− +𝟏
𝟐 𝟐
=𝟐 𝒙 + 𝑪
Example 2. Evaluate න൫𝟒𝒙𝟑 + 𝟑𝒙 − 𝟏)𝒅𝒙 .
Distribute 𝒅𝒙 and integrate To check:
each term separately. Evaluate the differential
of the function.
= න൫𝟒𝒙𝟑 𝒅𝒙 + 𝟑𝒙𝒅𝒙 − 𝐝𝒙)
𝟐
𝟑𝒙
𝒅 𝒙𝟒 + −𝒙+𝑪 = ൫𝟒𝒙𝟑 + 𝟑𝒙 − 𝟏)𝒅𝒙
= න𝟒𝒙𝟑 𝒅𝒙 + න𝟑𝒙 𝒅𝒙 − න𝒅𝒙 𝟐
𝟑
𝟒𝒙𝟑 𝒅𝒙 + 𝟐𝒙𝒅𝒙 − 𝒅𝒙 = ൫𝟒𝒙𝟑 + 𝟑𝒙 − 𝟏)𝒅𝒙
= 𝟒 න𝒙𝟑 𝒅𝒙 + 𝟑 න𝒙 𝒅𝒙 − න 𝒅𝒙 𝟐
൫𝟒𝒙𝟑 + 𝟑𝒙 − 𝟏)𝒅𝒙 = ൫𝟒𝒙𝟑 + 𝟑𝒙 − 𝟏)𝒅𝒙
𝟑+𝟏 𝟏+𝟏
= 𝟒∙ 𝒙 𝒙
+ 𝟑∙ −𝒙 +𝑪
𝟑+𝟏 𝟏+𝟏
𝟐
𝟑𝒙
= 𝒙𝟒 + −𝒙+𝑪
𝟐
𝟑 𝒅𝒙
Ex. 3. Evaluate න
𝟏 − 𝟐𝒙 𝟓
Power Formula;
= 𝟑 න 𝟏 − 𝟐𝒙 −𝟓 𝒅𝒙
𝒏+𝟏
𝒖
න𝒖𝒏 𝒅𝒖 = +𝑪
apply PF;𝒏 = −𝟓 𝒏+𝟏
𝒖 = 𝟏 – 𝟐𝒙
𝒅𝒖 = −𝟐𝒅𝒙
The new function,
𝟏 −𝟓
= − = 𝟑 න 𝟏 − 𝟐𝒙 (−𝟐𝒅𝒙)
𝟐

−𝟓 + 𝟏
𝟑 𝟏 − 𝟐𝒙
= − +𝑪
𝟐 −𝟓 + 𝟏
𝟑 −𝟒
= 𝟏 − 𝟐𝒙 +𝑪
𝟖
𝟐
Example 4. Evaluate න 𝒙𝟑 − 𝟏 𝒅𝒙 .

Expand the binomial;


Try to apply PF;
𝟐
න 𝒙𝟑 −𝒏𝟏= 𝒅𝒙
𝟐 = න 𝒙𝟔 − 𝟐𝒙𝟑 + 𝟏 𝒅𝒙

𝒖 = 𝒙𝟑 − 𝟏
= න𝒙𝟔 𝒅𝒙 − 𝟐 න 𝒙𝟑 𝒅𝒙 + න 𝒅𝒙
𝒅𝒖 = 𝟑𝒙𝟐 𝒅𝒙
𝟕 4
= 𝒙 − 𝟐∙ 𝒙 +𝒙 +𝑪
𝟕 𝟒
𝟐
The new function, න(𝒙𝟑 − 𝟏൯ (𝟑𝒙𝟐 𝒅𝒙)
𝒙 𝟕 𝟏 4
= − 𝒙 +𝒙 +𝑪
𝟕 𝟐
𝟐𝒂 𝒅𝒙
Example 5. Evaluate න 𝒖𝒏+𝟏
𝟒𝒂 − 𝟑𝒙 න𝒖𝒏 𝒅𝒖 = +𝑪
𝒏+𝟏
𝟐𝒂 𝒅𝒙 −𝟏Τ𝟐
න = 𝟐𝒂 න 𝟒𝒂 − 𝟑𝒙 𝒅𝒙
𝟒𝒂 − 𝟑𝒙
𝟏
Try to Power Formula(PF); − +𝟏
𝟐𝒂 𝟒𝒂 − 𝟑𝒙 𝟐
𝟏 = − +𝑪
𝒏 = − 𝟑 𝟏
𝟐 − +𝟏
𝟐
𝒖 = 𝟒𝒂 − 𝟑𝒙
𝒅𝒖 = −𝟑 𝒅𝒙 𝟒𝒂 𝟏
= − 𝟒𝒂 − 𝟑𝒙 𝟐 +𝑪
𝟑
The new function,
𝟏 −𝟏Τ𝟐
= − 𝟐𝒂න 𝟒𝒂 − 𝟑𝒙 (−𝟑𝒅𝒙൯
𝟑
𝟑
𝒙 𝒙
Example 6. Evaluate න 𝒔𝒊𝒏 𝒄𝒐𝒔 𝒅𝒙
𝟐 𝟐
Solution:
Apply PF: The new function,
𝒏 = 𝟑 𝒙 𝟑 𝟏 𝒙
= 𝟐 න 𝒔𝒊𝒏 ∙ 𝒄𝒐𝒔 𝒅𝒙
𝒙 𝟐 𝟐 𝟐
𝒖 = 𝒔𝒊𝒏
𝟐 𝒙 𝟒
𝒔𝒊𝒏
𝒙 𝒙 =𝟐∙ 𝟐 + 𝑪
𝒅𝒖 = 𝒄𝒐𝒔 ∙𝒅 𝟒
𝟐 𝟐
𝒙 𝟏 𝟏 𝒙
𝒅𝒖 = 𝒄𝒐𝒔 ∙ 𝒅𝒙 = 𝒔𝒊𝒏𝟒
+𝑪
𝟐 𝟐 𝟐 𝟐
𝟏 𝒙
= 𝒄𝒐𝒔 𝒅𝒙
𝟐 𝟐
Example 7. Evaluate න 𝒆𝒚 𝟒 − 𝒆𝒚 𝟓/𝟐 𝒅𝒚 .
Solution:
Apply PF:
𝒏 = 𝟓Τ𝟐
𝒖 = 𝟒 − 𝒆𝒚
𝒅𝒖 = −𝒆𝒚 𝒅𝒚
The new function,
𝟓Τ𝟐
= (−𝟏) න 𝟒 − 𝒆𝒚 −𝒆𝒚 𝒅𝒚
𝟓
+𝟏
𝒚 𝟐
𝟒− 𝒆
= −𝟏 𝟓 +𝑪
+𝟏
𝟐
𝟐 𝒚
𝟕
= − 𝟒− 𝒆 𝟐 +𝑪
𝟕
𝟐 𝒍𝒏𝟏/𝟒 𝟏 − 𝒙
Example 9. Evaluate න 𝒅𝒙
𝟏−𝒙
𝒍𝒏𝟏/𝟒 𝟏 − 𝒙 𝟓
Solution: = 𝟐න 𝒅𝒙
𝟏−𝒙 𝐥𝐧 𝟏 − 𝒙 𝟒
= −𝟐 ∙ +𝑪
Using PF; 𝟓
𝟏 𝟒
𝒏=
𝟒
𝟖 𝟓
𝒖 = 𝒍𝒏 𝟏 − 𝒙 = − 𝐥𝐧 𝟏 − 𝒙 𝟒 +𝑪
𝟓
−𝒅𝒙
𝒅𝒖 =
𝟏−𝒙
The new function,

𝟏Τ𝟒
−𝒅𝒙
= (−𝟏) 𝟐 න 𝒍𝒏 𝟏 − 𝒙
𝟏−𝒙
Example 10. න 𝟕𝒙𝟑 + 𝟒𝒙𝟐 𝒅𝒙.

න 𝟕𝒙𝟑 + 𝟒𝒙𝟐 𝒅𝒙 = න𝟕𝒙𝟑 𝒅𝒙 + න𝟒𝒙𝟐 𝒅𝒙

= 𝟕 න𝒙𝟑 𝒅𝒙 + 𝟒 න𝒙𝟐 𝒅𝒙

𝒙𝟒 𝒙𝟑
=𝟕∙ + 𝟒∙ + 𝑪
𝟒 𝟑

𝟕 𝟒 𝟒 𝟑
= 𝒙 + 𝒙 + 𝑪
𝟒 𝟑
Example 10. Evaluate න 𝒕𝒂𝒏 𝜽 𝒍𝒏 𝒔𝒆𝒄 𝜽 𝒅𝜽 .

Solution: Using PF; 𝒏=𝟏


𝒖 = 𝒍𝒏 𝐬𝐞𝐜 𝜽
𝒅(𝐬𝐞𝐜 𝜽) 𝒔𝒆𝒄 𝜽 𝒕𝒂𝒏 𝜽 𝒅𝜽
𝒅𝒖 = =
𝐬𝐞𝐜 𝜽 𝒔𝒆𝒄 𝜽
= 𝒕𝒂𝒏 𝜽 𝒅𝜽

The new function,

𝟏 𝐭𝐚𝐧 𝜽
= න 𝒍𝒏 𝐬𝐞𝐜 𝜽 𝒅𝜽

𝟏 𝟐
= 𝒍𝒏 𝐬𝐞𝐜 𝜽 + 𝑪
𝟐
𝒍𝒏 𝒚 𝒄𝒐𝒔 𝟒𝜽
Ex. 11. Evaluate න 𝒅𝜽 . Alternative Solution:
𝒄𝒔𝒄 𝟒𝜽
Solution: = 𝒍𝒏 𝒚 න 𝒄𝒐𝒔 𝟒𝜽 𝒔𝒊𝒏 𝟒𝜽 𝒅𝜽 .
Since the variable of integration is 𝜽 ,
𝒍𝒏 𝒚 is considered a constant. Using PF;
𝒄𝒐𝒔 𝟒𝜽 𝒏=𝟏
= 𝒍𝒏 𝒚 න 𝒅𝜽
𝒄𝒔𝒄 𝟒𝜽 𝒖 = 𝒔𝒊𝒏 𝟒𝜽
= 𝒍𝒏 𝒚 න 𝒄𝒐𝒔 𝟒𝜽 𝒔𝒊𝒏 𝟒𝜽 𝒅𝜽 𝒅𝒖 = 𝟒 𝐜𝐨𝐬 𝟒𝜽 𝒅𝜽
𝟏
Using PF; 𝒏=𝟏 = 𝒍𝒏 𝒚න 𝒔𝒊𝒏 𝟒𝜽 𝟒𝒄𝒐𝒔 𝟒𝜽𝒅𝜽
𝒖 = 𝐜𝐨𝐬 𝟒𝜽 𝟒
𝒅𝒖 = −𝟒 𝐬𝐢𝐧 𝟒𝜽 𝒅𝜽 𝟏 𝒔𝒊𝒏𝟐 𝟒𝜽
𝟏 = 𝒍𝒏 𝒚 ∙ +𝑪
𝟒 𝟐
= − 𝒍𝒏 𝒚න 𝒄𝒐𝒔 𝟒𝜽 −𝟒𝒔𝒊𝒏 𝟒𝜽𝒅𝜽
𝟒 𝟏
= 𝒍𝒏 𝒚 𝒔𝒊𝒏𝟐 𝟒𝜽 + 𝑪
𝟏 𝒄𝒐𝒔𝟐 𝟒𝜽 𝟏 𝟖
= − 𝒍𝒏 𝒚 ∙ + 𝑪 = − 𝒍𝒏 𝒚 𝒄𝒐𝒔𝟐 𝟒𝜽 + 𝑪
𝟒 𝟐 𝟖